2018
DOI: 10.1590/1678-4685-gmb-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of 3-Methylcrotonylglycinuria in an Italian asymptomatic girl

Abstract: Abstract3-Methylcrotonylglycinuria is an organic aciduria resulting from deficiency of 3-methylcrotonyl-CoA carboxylase (3-MCC), a biotin-dependent mitochondrial enzym carboxylating 3-methylcrotonyl-CoA to 3-methylglutaconyl-CoA during leucine catabolism. Its deficiency, due to mutations on MCCC1 and MCCC2 genes, leads to accumulation of 3-methylcrotonyl-CoA metabolites in blood and/or urine, primarily 3-hydroxyisovaleryl-carnitine (C5-OH) in plasma and 3-methylcrotonyl-glycine (3-MCG) and 3-hydroxyisovaleric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“… 2 53 Methylcrotonoyl-CoA carboxylase also relates synthesis of fatty acid with Acetyl-CoA carboxylase. 54 Contrary to the previous research indicating that two enzymes in this reaction are inhibited by glucagon 2 53 and interact with Gcg mRNA, we speculate that these enzymes might be involved in inhibition of Gcg mRNA translation or activation of Gcg mRNA decay. Although there are no studies showing that these carboxylases bind RNA directly, they may interact with Gcg mRNA via other RNA-binding proteins.…”
Section: Discussioncontrasting
confidence: 97%
“… 2 53 Methylcrotonoyl-CoA carboxylase also relates synthesis of fatty acid with Acetyl-CoA carboxylase. 54 Contrary to the previous research indicating that two enzymes in this reaction are inhibited by glucagon 2 53 and interact with Gcg mRNA, we speculate that these enzymes might be involved in inhibition of Gcg mRNA translation or activation of Gcg mRNA decay. Although there are no studies showing that these carboxylases bind RNA directly, they may interact with Gcg mRNA via other RNA-binding proteins.…”
Section: Discussioncontrasting
confidence: 97%
“… 4 MCC deficiency can lead to the disorder of leucine metabolism, which can be manifested in a variety of phenotypes, including neurological disorders, infant death and asymptomatic adults. 5 8 A mouse study has shown that MCCC2 is associated with obesity, insulin resistance and dyslipidemia. 9 In addition, MCC deletion indicates changes in glycolysis, TCA cycle, OXPHOS, gluconeogenesis, β-oxidation and branched chain fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…PCC, MCC, and PC are all located in the mitochondrial matrix. PCC and MCC enzymes regulate critical steps of amino acid catabolism (and odd-chain FAs for PCC) by respectively producing methylmalonyl-CoA from propionyl-CoA for the catabolism of isoleucine, methionine, valine and threonine [ 106 ] ( Figure 1 ), and 3-methylglutaconyl-CoA from 3-methylcrotonyl-CoA for leucine and isovaleric acid catabolism [ 107 ]. PC also converts pyruvate to oxaloacetate that can be used to replenish the TCA cycle or for the initiation of gluconeogenesis (in liver and kidney) or lipogenesis (adipose tissue, liver as well as brain) [ 107 ].…”
Section: Energy Metabolism and B Vitaminsmentioning
confidence: 99%